2011
DOI: 10.1109/surv.2011.041311.00156
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Adversaries in Sensor Networks: A Survey of Theoretical Models and Algorithmic Approaches for Tolerating Malicious Interference

Abstract: Interference is an unavoidable property of the wireless communication medium and, in sensor networks, such interference is exacerbated due to the energy-starved nature of the network devices themselves. In the presence of antagonistic interference, reliable communication in sensor networks becomes an extremely challenging problem that, in recent years, has attracted significant attention from the research community.This survey presents the current state of affairs in the formulation of theoretical models for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…Moreover, recent works in [10,12] have practically demonstrated that flexible and reliable software-defined reactive jamming is feasible by designing and implementing a reactive jammer against existing wireless networks. However, most existing research either does not take into account the energy expenditures of the adversary and the legitimate nodes or it consider the energy expenditures of the legitimate nodes and the adversary in isolation (see [13][14][15][16] and [17], and references therein). In autonomous scenarios where energy is a scarce resource for both the legitimate competing nodes and the adversary it is reasonable to consider a notion of relative cost in terms of energy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent works in [10,12] have practically demonstrated that flexible and reliable software-defined reactive jamming is feasible by designing and implementing a reactive jammer against existing wireless networks. However, most existing research either does not take into account the energy expenditures of the adversary and the legitimate nodes or it consider the energy expenditures of the legitimate nodes and the adversary in isolation (see [13][14][15][16] and [17], and references therein). In autonomous scenarios where energy is a scarce resource for both the legitimate competing nodes and the adversary it is reasonable to consider a notion of relative cost in terms of energy.…”
Section: Related Workmentioning
confidence: 99%
“…Note that in practice to conserve energy of distributed TX/RX pairs, each TX/RX pair should be put to sleep mode as soon as there is no more data to send/receive, and should be put to awake mode as soon as new packets become ready. Several distributed sleep/wakeup scheduling algorithms to conserve energy are presented in the literature (see [17,37] and references therein) and the study of such algorithms is beyond the scope of this paper.…”
Section: A Network Modelmentioning
confidence: 99%
“…According to our thorough investigation in the area, there is currently no comprehensive survey on the key revocation mechanisms in wireless sensor network. A good number of surveys on sensors and wireless sensor networks are available today focusing on the various aspects of security (Djenouri et al, 2005;Wang et al, 2006;Walters et al, 2007;Zhou et al, 2008;Li and Gong, 2008;Chen et al, 2009;Sen, 2009;Zhang et al, 2010;Abduvaliyev et al, 2013), data aggregation techniques (Rajagopalan and Varshney, 2006;Wang and Liu, 2011), power control issues (Pantazis and Vergados, 2007), multimedia streaming in WSN (Misra et al, 2008;Seema and Reisslein, 2011;Ehsan and Hamdaoui, 2012), Medium Access Control (MAC) related issues (Bachir et al, 2012;Suriyachai et al, 2012;Dong and Dargie, 2013;Doudou et al, 2013;Huang et al, 2013), challenges and approaches of providing Operating System (OS) support for WSN (Dong et al, 2010), Computational Intelligence in WSN (Kulkarni et al, 2011), energy harvesting in WSN (Sudevalayam and Kulkarni, 2011), energy-efficiency issues (Ehsan and Hamdaoui, 2012;Aziz et al, 2013;Pantazis et al, 2013), wireless communications, interference, and connectivity issues (Young and Boutaba, 2011;Kashi and Sharifi, 2013), reference structure in sensor systems (Peng and Xiao, 2012), mobility issues (Dong and Dargie, 2013), Quality of Service (QoS) issues (Ehsan and Hamdaoui, 2012), routing issues (Li et al, 2011;Ehsan and ...…”
Section: Significance and Implication Of This Workmentioning
confidence: 99%
“…There also exist several interesting results on protocols that are robust to more complex or even adversarial interference (see, e.g., [7] or [29] for a nice overview). There are two basic approaches in the literature.…”
Section: Related Workmentioning
confidence: 99%